2018
DOI: 10.1186/s12905-018-0567-3
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ autonomy and childhood stunting: evidence from semi-urban communities in Lao PDR

Abstract: BackgroundChildhood stunting (height-for-age z-scores below − 2), a form of chronic undernutrition, remains a global health burden. Although a growing literature has examined the association between mothers’ autonomy and childhood stunting, these studies have been limited to countries in South Asia or Sub-Saharan Africa where women have relatively lower social status than do men. Little research has analyzed the effect of mothers’ autonomy on childhood stunting in Lao PDR, where women’s social status is relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 25 publications
(27 reference statements)
5
33
0
1
Order By: Relevance
“…is is in agreement with studies conducted in Butajira, Benin, and analysis of sub-Saharan demographic and health survey data [13,19,39]. However, freedom of mobility had no significant association with stunting in the study conducted at Jimma, Ethiopia, and Lao PDR [42,43]. e possible reason could be due to cross cultural nature of empowerment domains from area to area [13,[44][45][46].…”
Section: Discussionsupporting
confidence: 89%
“…is is in agreement with studies conducted in Butajira, Benin, and analysis of sub-Saharan demographic and health survey data [13,19,39]. However, freedom of mobility had no significant association with stunting in the study conducted at Jimma, Ethiopia, and Lao PDR [42,43]. e possible reason could be due to cross cultural nature of empowerment domains from area to area [13,[44][45][46].…”
Section: Discussionsupporting
confidence: 89%
“…For example, in line with our finding, Imai et al [ 45 ], Alkire et al [ 46 ] and Salawu et al [ 37 ] reported a significant association between women’s decision-making power and the reduction of childhood stunting. On the contrary, women’s decision-making power was not significantly associated with childhood stunting in Mozambique [ 23 ] in Lao People’s Democratic Republic [ 47 ]. Also, being decision-makers in the household had no association with child malnutrition in Pakistan [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adolescent or young mothers experience a greater lack of access to essential maternal and child health services (Delprato & Akyeampong, 2017) and have lower decision-making autonomy than older mothers (Kamiya et al, 2018). Importantly, the adverse effects of these disadvantages on child nutritional status would be greater when children are younger.…”
Section: Discussionmentioning
confidence: 99%